3D Neural Network Composed of Neurospheroid and Bionanohybrid on Microelectrode Array to Realize the Spatial Input Signal Recognition in Neurospheroid (Small Methods 8/2022). Issue 8 (17th August 2022) - Yoon, Jinho; Kim, Hyun‐Woong; Shin, Minkyu; Lim, Joungpyo; Lee, Ji‐Young; Lee, Sang‐Nam; Choi, Jeong‐Woo
Abstract : Front Cover In article number 2200127, Lee, Choi, and co‐workers proposed a novel method for developing the in vitro 3D neural network composed of the bionanohybrid, 3D neurospheroid and the microelectrode array which correspond to 'Input layer', 'Hidden layer', and 'Output layer' in the classical neural network, and the spatially recognized electrophysiological output signals are realized by input signals in the in vitro 3D neural network.